Hálsagígar Eruption: Tephra dispersal, geochemistry, volume and age - Rebecca Feldman 1996- (2020)
A study on dispersal, volume, geochemistry, and age of tephra from Hálsagígar crater – row, Rauðhóll crater and Botnahraun lava in South Iceland demonstrates that they all erupted in a single eruption. This eruption was on an 8 km long discontinuous fissure on the SW part of the Grímsvötn volcanic system. The Hálsagígar tephra (HAG) and Rauðhóll tephra (RAG) occupy the same stratigraphic level in the regional tephrochronology and were dated to ~5300 years ago using SAR between marker tephra layers. HAG was deposited on Botnahraun while the lava was hot and moving, confirming simultaneous eruption of tephra and lava. HAG dispersed to the west and south, having a volume of ~0.03 km3. Grain characteristics indicate that the explosive activity at Hálsagígar was strombolian with eruption cloud reaching seven km above source. Dispersal and fragmentation (D/F%) classify it as Sub-Plinian. The RAG forms a narrow lobe toward west and lies on top of HAG where found together. Grain characteristics of RAG change with time from ash-rich, bedded, phreatomagmatic tephra to coarser scoria, indicating that water affected the early explosive phases at Rauðhóll crater. The volume of RAG is small and was not calculated. The geochemistry of the HAG and RAG is typical for the Grímsvötn system. The HAG shows no systematic changes with time but some changes with time are observed in the RAG. The geochemistry of the Botnahraun lava was obtained by XRF on whole-rock samples in earlier studies but agrees reasonably with the tephra composition given different analytical method.